Disruption of the homeodomain transcription factor orthopedia homeobox (Otp) is associated with obesity and anxiety - Lee Moir; Elena G. Bochukova; Rebecca Dumbell; Gareth Banks; Rasneer S. Bains; Patrick M. Nolan; Cheryl Scudamore; Michelle Simon; Kimberly A. Watson; Julia Keogh; Elana Henning; Audrey Hendricks; et al. (Elsevier, 2017)
Objective: Genetic studies in obese rodents and humans can provide novel insights into the mechanisms involved in energy homeostasis. Methods: In this study, we genetically mapped the chromosomal region underlying the development of severe obesity in a mouse line identified as part of a dominant N-ethyl-N-nitrosourea (ENU) mutagenesis screen. We characterized the metabolic and behavioral phenotype of obese mutant mice and examined changes in hypothalamic gene expression. In humans, we examined genetic data from people with severe early onset obesity. Results: We identified an obese mouse heterozygous for a missense mutation (pR108W) in orthopedia homeobox (Otp), a homeodomain containing transcription factor required for the development of neuroendocrine cell lineages in the hypothalamus, a region of the brain important in the regulation of energy homeostasis. OtpR108W/+ mice exhibit increased food intake, weight gain, and anxiety when in novel environments or singly housed, phenotypes that may be partially explained by reduced hypothalamic expression of oxytocin and arginine vasopressin. R108W affects the highly conserved homeodomain, impairs DNA binding, and alters transcriptional activity in cells. We sequenced OTP in 2548 people with severe early-onset obesity and found a rare heterozygous loss of function variant in the homeodomain (Q153R) in a patient who also had features of attention deficit disorder. Conclusions: OTP is involved in mammalian energy homeostasis and behavior and appears to be necessary for the development of hypothalamic neural circuits. Further studies will be needed to investigate the contribution of rare variants in OTP to human energy homeostasis.